The Impact of Loan Losses Provisions on Profitability in Conventional Private Commercial Banks listed on the Damascus Securities Exchange - ضاهر حنان (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This research aimed to examine the impact of loan loss provisions on the profitability of traditional private commercial banks operating in Syria. Based on annual Panel data for /11/ banks during the period 2010-2018, we study and analyze the study variables. The dependent variable which expresses the profitability of the studied banks was measured by the return on equity (ROE), Whereas, the independent variable which expresses loan losses provisions (LLP) was measured by the " ratio of loan losses provisions to total direct credit facilities". Preliminary tests are applied to test for the Stationarity of the selected variables, then we compare panel models using a number of tests, such as F test Hausman test and the Lagrange multiplier (LM) test. A Generalized Least Squares is fitted to assess the potential effects of the loan loss provisions in the profitability of the considered banks. The results showed that the provisions for loan losses had a negative impact on the profitability of the studied banks.